Identifying Causal and Contextual Factors Affecting the Efficiency of Distance Education - Shabnam Khoramirooz; Abbas Gholtash; Fatemeh Ahmadbeigi (Iranian Evolutionary Educational Psychology Journal)
Objective: The primary aim of the current research endeavor was to discern the determinants influencing the efficacy of distance education Methods: In this investigation, a qualitative methodological approach was employed. The sampling within the qualitative component was executed intentionally through the expert network methodology, wherein 13 individuals contributed to the interview process. To evaluate the variables pertinent to the research, a semi-structured interview format was utilized to examine the factors influencing the assessment of the efficacy of distance education. The agreement coefficient of 0.78 obtained from the interviews signifies a high level of reliability associated with the research instruments employed. The analysis of qualitative data was conducted utilizing open, selective, and theoretical coding techniques. Results: The conclusive findings of the study, as derived from the interviews, revealed that the determinants influencing the assessment of the efficacy of distance education include: 1) Causal factors (modern technology; perceived ease of use; suitable educational software; qualified instructors; learner motivation and engagement); 2) Contextual factors (legislative frameworks and regulations, adequate technological infrastructure, support mechanisms for distance learning, proficiency in information technology, and the diversity and applicability of educational content). Conclusions: Findings support the role of contextual and causal factors in the effectiveness of distance learning.